2020
DOI: 10.3389/fphys.2019.01609
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling and Nutritional Regulation in the Context of Poultry Feather Growth and Regeneration

Abstract: The normal growth and regeneration of feathers is important for improving the welfare and economic value of poultry. Feather follicle stem cells are the basis for driving feather development and are regulated by various molecular signaling pathways in the feather follicle microenvironment. To date, the roles of the Wnt, Bone Morphogenetic Protein (BMP), Notch, and Sonic Hedgehog (SHH) signaling pathways in the regulation of feather growth and regeneration are among the best understood. While these pathways reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Adult chicken feathers undergo a cyclical development pattern, consisting of anagenesis, regression, and rest. Normal feather growth and regeneration play a crucial role in improving the welfare and economic value of poultry [18]. However, normal laying hens typically experience a loss of 10% to 15% of their feathers by 40 weeks of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…Adult chicken feathers undergo a cyclical development pattern, consisting of anagenesis, regression, and rest. Normal feather growth and regeneration play a crucial role in improving the welfare and economic value of poultry [18]. However, normal laying hens typically experience a loss of 10% to 15% of their feathers by 40 weeks of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…Methionine injected in ovo increased the density and diameter of chicken-embryo feather follicles [ 43 ]. Methionine has been found to promote follicle and feather growth in developing chick embryos by activating the Wnt/β-catenin signaling pathway [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is notable that the promoted effects were driven by the injection dose and the time after receiving the injection. The economic value of a feather determines that a higher feather yield, feather quality, and growth rate are beneficial to the goose industry ( Chen, et al, 2020a ). Although strategies on nutrition and management are improving this status, some genetic and physiological bases still are limited.…”
Section: Discussionmentioning
confidence: 99%
“…During the developmental process of feather formation, transduction molecules, transcription factors, and other genetic factors synergistically and/or independently influence the dynamic morphogenesis of skin and feather follicles ( Inamatsu, et al, 2006 ; Jiang, et al, 2011 ). Studies have confirmed that the Wnt, TGF-β, MAPK, and BMP signaling pathways are candidate morphogens associated with feather follicle development during embryogenesis ( Chen, et al, 2020a ; Ji, et al, 2021 ; Zheng, et al, 2020 ). Particularly, the Wnt is the initial signal for feather follicle development and participates in each stage of feather follicle morphogenesis, such as placode formation, dermal papillae function, feather follicle cycle, and proliferation and differentiation of feather follicle stem cells ( Andl, et al, 2002 ; García de Herreros and Duñach, 2019 ; Huelsken, et al, 2001 ; Kaushal, et al, 2015 ; Nusslein-Volhard and Wieschaus, 1980 ; Telerman, et al, 2017 ; Tsai, et al, 2014 ; Wong, et al, 1994 ; Wu, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 91%